Lin28a Regulates Germ Cell Pool Size and Fertility123. (24th April 2013) - Shinoda, Gen; De Soysa, T. Yvanka; Seligson, Marc T.; Yabuuchi, Akiko; Fujiwara, Yuko; Huang, Pei Yi; Hagan, John P.; Gregory, Richard I.; Moss, Eric G.; Daley, George Q.
Abstract Overexpression of LIN28A is associated with human germ cell tumors and promotes primordial germ cell (PGC) development from embryonic stem cells in vitro and in chimeric mice. Knockdown of Lin28a inhibits PGC development in vitro, but how constitutional Lin28a deficiency affects the mammalian reproductive system in vivo remains unknown. Here, we generated Lin28a knockout (KO) mice and found that Lin28a deficiency compromises the size of the germ cell pool in both males and females by affecting PGC proliferation during embryogenesis. Interestingly however, in Lin28a KO males, the germ cell pool partially recovers during postnatal expansion, while fertility remains impaired in both males and females mated to wild‐type mice. Embryonic overexpression of let‐7, a microRNA negatively regulated by Lin28a, reduces the germ cell pool, corroborating the role of the Lin28a/let‐7 axis in regulating the germ lineage. STEM CELLS 2013;31:1001–1009